Świerzbiączka guzkowa leczona dożylnie immunoglobulinami - Durmaz, Koray; Ataseven, Arzu; Ozer, Ilkay; Fındık, Sıddıka (Dermatology Review/Przegląd Dermatologiczny, 2022)
Prurigo nodularis is a chronic skin disease, especially seen in middle-aged women adults. It is characterized by symmetric, pruritic hyperkeratotic nodules and papules on the extensor surfaces [1]. Prurigo nodularis patients can suffer from repeated itching and scratching cycles or intensive pruritus. The etiology of prurigo nodularis is not clear. The lesions can be seen primarily or be caused by another pruritic condition. The trigger can be other dermatoses such as atopic dermatitis or secondary pruritus due to another systemic disease such as chronic kidney disease, jaundice, malignancies, etc. The interaction between cutaneous nerve fibers and immune cells can play a crucial role in pathogenesis [2]. Treatment options for prurigo nodularis are limited by studies. Most of the studies aim at symptomatic relief of patients [3].